Tahfiz psychogeography of the marginals: reimagining self and place through narratives - Mohd Muzhafar Idrus,; Normazla Ahmad Mahir,; Habibah Ismail,; Noornajihan Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In line with James Sidaway's insistence on the psychogeographical integration of nature with narratives across rural communities, this article investigates 'on-the-ground' narratives by the marginals. Psychogeography is often defined as creative studies of space to alter conventional ways of viewing things. The marginals studied in this article were poor communities situated at a rural Tahfiz centre in the northwest of Peninsular Malaysia. Tahfiz centres are plenty across Malaysian states, but they are generally defined as Muslim worshipping and learning spaces inhabited by the young and old whose sustenance relies on the generosity of donors. By analysing these ‘on-the-ground’ words, readings, and experiences by Tahfiz marginals situated at a de-urbanised locale, we firstly suggest that their ‘psychogeographical journey’ with said centre puts them in a reflective position that is, in part, illustrated by their consenting and commendatory attachment as an impact of their walking in the said centre. Secondly, we extend this interrogation on the psychogeographical experience of self-and-place attachment by proposing an alternative theoretical model, Tahfiz psychogeography. Tahfiz psychogeography, a model that challenges the idea of Tahfiz centres being unsafe and unaccommodating, emphasises instead the construction and preservation of social engagement. Tahfiz's psychogeography aims to create a strong sense of connectedness and unity by integrating individuals, encouraging flexibility and inclusion, and focusing on a panoptic vision of communal relations.